Clinical Experience with Frameless Neuronavigation Guided Biopsy for Intracranial Space Occupying Lesion - Thulung, Suraj; Bishokarma, Suresh; Lohani, Subash; Shrestha, Dinuj; Aryal, Binit; Napit, Munu (Nepal Journal of Neuroscience, 2019)
Biopsy is mandatory for histological diagnosis of non-resectable brain tumors. Of various techniques, neuronavigation guided biopsy provides intraoperative real-time reference and allows biopsy from multiple trajectories. The aim of this study is to assess the efficacy and accuracy of frameless neuronavigation biopsy.We retrospectively reviewed the medical archives of patients with intracranial space occupying lesion who underwent frameless neuronavigation biopsy at our institute between 2016 to 2018. All operations were performed under general anesthesia. Data were analyzed by SPSS version 20. P value of